Enhancement of exercise capacity in the heat with repeated menthol-spray application - Barwood, M. J.; Kupusarevic, J.; Goodall, S. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Exercise performance is impaired in the heat, and a contributing factor to this decrement is thermal discomfort. Menthol spraying of skin is one means of alleviating thermal discomfort but has yet to be shown to be ergogenic using single-spray applications. The authors examined whether repeated menthol spraying could relieve thermal discomfort, reduce perception of exertion, and improve exercise performance in hot (35°C), dry (22% relative humidity) conditions, hypothesizing that it would. Methods: A total of 8 trained cyclists completed 2 separate conditions of fixed-intensity cycling (50% maximal power output) for 45 min before a test to exhaustion (TTE; 70% maximal power output) with 100 mL of menthol spray (0.20% menthol) or control spray applied to the torso after 20 and 40 min. Perceptual (thermal sensation, thermal comfort, and rating of perceived exertion) performance (TTE duration), thermal variables (skin temperature, rectal temperature, and cardiac frequency), and sweating were measured. Data were compared using analysis of variance to .05 alpha level. Results: Menthol spray improved thermal sensation (cold sensation cf warm/hot after first spraying; P = .008) but only descriptively altered thermal comfort (comfortable cf uncomfortable; P = .173). Sweat production (994 [380] mL cf 1180 [380] mL; P = .020) and sweat rate (827 [327] mL/h cf 941 [319] mL·h-1; P = .048) lowered. TTE performance improved (4.6 [1.74] cf 2.4 [1.55] min; P = .004). Menthol-spray effects diminished despite repeated applications, indicating increased contribution of visceral thermoreceptors to thermal perception. Conclusion: Repeated menthol spraying improves exercise capacity but alters thermoregulation, potentially conflicting behavioral and thermoregulatory drivers; care should be taken with its use. Carrying and deploying menthol spray would impose a logistical burden that needs consideration against performance benefit.